Refractory Head and Neck Lymphatic Malformation in Infants Treated With Sirolimus: A Case Series - Wu, Changhua; Song, Dan; Guo, Lei; Wang, Liang (Frontiers in Oncology, 2021)
Background: Extensive and complex head and neck lymphatic malformations (LMs) are challenging to manage through traditional therapy. The purpose of this retrospective study was to assess the efficacy and safety of sirolimus in infants with refractory head and neck LM. Methods: Sirolimus was administered orally on a continuous dosing schedule. Patients were seen every month for the first three months and then subsequently every three months. The primary endpoints were safety and efficacy based on clinical and radiological evaluations. Results: Eight patients, refractory to standard care, were enrolled and received sirolimus continuously. After 12 months of follow-up, the response and safety to medication was evaluated: all patients experienced reductions in LM bulk, ranging from modest to significant. Some minor adverse effects were reported: mouth sores, eczema, gastrointestinal reaction, dyslipidemia, and neutropenia. Conclusion: Sirolimus was efficient in children with refractory head and neck LM and was well tolerated. Long-term follow-up, durability of response, and coordination of sirolimus prior to procedural therapies need further study.